2014
DOI: 10.1371/journal.pone.0100978
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Up-Regulation of CXCL10 by Virus and IFN γ in Human Airway Epithelial Cells

Abstract: Airway epithelial cells are the first line of defense against viral infections and are instrumental in coordinating the inflammatory response. In this study, we demonstrate the synergistic stimulation of CXCL10 mRNA and protein, a key chemokine responsible for the early immune response to viral infection, following treatment of airway epithelial cells with IFN γ and influenza virus. The synergism also occurred when the cells were treated with IFN γ and a viral replication mimicker (dsRNA) both in vitro and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 29 publications
3
20
0
1
Order By: Relevance
“…In PIN samples, we found CD3 + T cells and CD3 − immune cells positive for CXCL10 in TLO (Figure 11A). Consistent with previous reports (61, 62), CXCL10 + epithelial cells were detected in a few tumor locations in PIN specimens (Figure 11E). At intermediate stages of prostate cancer, a considerable number of CXCL10 + CD3 + T cells were located inside TLO (Figure 11B), and multiple epithelial cells were positive for CXCL10 in tumor areas (Figure 11F).…”
Section: Resultssupporting
confidence: 93%
“…In PIN samples, we found CD3 + T cells and CD3 − immune cells positive for CXCL10 in TLO (Figure 11A). Consistent with previous reports (61, 62), CXCL10 + epithelial cells were detected in a few tumor locations in PIN specimens (Figure 11E). At intermediate stages of prostate cancer, a considerable number of CXCL10 + CD3 + T cells were located inside TLO (Figure 11B), and multiple epithelial cells were positive for CXCL10 in tumor areas (Figure 11F).…”
Section: Resultssupporting
confidence: 93%
“…Our data also demonstrate the upregulation of IP-10 upon HIV-1 (WT) infection (Fig. 3C), which is also dependent on NF-B activation (105)(106)(107).These results suggest a link between Vpr-mediated NF-B activation in MDDCs and enhanced viral gene expression and proinflammatory cytokine secretion, which may act in vivo to enhance recruitment, activation, and infection of CD4 ϩ T cells, resulting in increased viral dissemination (Fig. 1E) (27,75,99).…”
Section: Discussionsupporting
confidence: 62%
“…We found that DQT, at low non-toxic concentrations ( Figure 1 ), inhibited CXCL10 expression in a dose-dependent manner, not only at the protein level ( Figure 2 a), but also at the level of transcription ( Figure 2 b). CXCL10 gene transcription is regulated by signaling pathways elicited by interferons β and γ, as well as by the NFκB transcription factor, whose activation is controlled by the IκB inhibitory protein [ 13 , 23 , 24 ]. Therefore, we wanted to determine which of these mechanisms is involved in the inhibition of CXCL10 gene expression by the DQT compound.…”
Section: Discussionmentioning
confidence: 99%